Foreign Experience in Assessing the Impact of the System of Inter-Budgetary Relations on the Level of Interregional Differentiation (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
The article describes the types of models of inter-budgetary relations classified in world practice, analyzes the foreign experience of the organization of the system of inter-budgetary relations, as well as their assessment at the level of interregional differentiation. It is concluded that there is no direct connection between the size of the transfer and the level of socio-economic development of the regions, which, in our opinion, is due to the fact that if all subjects are recipients of transfers or if the variation in the level of development of regions receiving transfers differs little from the variation in regions not receiving transfers, then interregional inequality is unlikely to change under the influence of these transfers.